Solid‐state microcellular high temperature vulcanized (HTV) silicone rubber foam with carbon dioxide - Yang, Qian; Yu, Haitao; Song, Lixian; Lei, Yajie; Zhang, Fengshun; Lu, Ai; Liu, Tao; Luo, Shikai (Journal of applied polymer science, 2017)
ABSTRACT A series of microcellular high temperature vulcanized (HTV) silicone rubber foams were prepared using CO2 as a physical blowing agent. Rheological properties, gas diffusive behavior, and foaming parameters of silicone rubber were investigated. The results show that saturation pressure has a significant effect on the diffusivity of CO2 in HTV silicone rubber matrix. The gas concentration and diffusivity increase from 2.45 wt % to 3.24 wt %, and from 1.62 × 10−5 cm2/s to 7.83 × 10−5 cm2/s as the saturation pressure increases from 2 MPa to 5 MPa, respectively. The value of the gas diffusivity in HTV silicone rubber is almost 1000 times higher than that of the gas diffusivity in polyetherimide (PEI) matrix. Additionally, microcellular HTV silicone rubber foams with the smallest cell diameter of 9.8 μm and cell density exceeding 108 cells/cm3 are achieved. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2017, 134, 44807.